Cost-Efficient Resilient Data Engineering Workloads Using Preemptible Resources - Shah, Vishal Mukeshbhai (International Journal of Computing and Engineering, 2025)
This article examines how organizations can optimize cloud computing costs through resilient data engineering workloads on preemptible resources. By leveraging discounted but ephemeral computing offerings from major cloud providers, enterprises can achieve significant cost reductions while maintaining operational reliability. The discussion covers the fundamental characteristics of preemptible computing resources, architectural patterns for resilient data processing, case studies of successful ETL workload optimizations, and applications for machine learning training. Key findings demonstrate that properly designed resilient architectures can withstand interruptions while preserving processing integrity, enabling organizations to harness substantial cost advantages through partitioning, checkpointing, and stateless processing patterns. The article further explores how these architectural approaches not only deliver direct economic benefits but also contribute to enhanced security postures, improved disaster recovery capabilities, and more efficient resource utilization across enterprise computing environments, providing a comprehensive framework for technical leaders seeking to balance cost optimization with operational resilience in increasingly complex cloud ecosystems.